The psychosocial determinants of the intention to avoid sexual engagement when intoxicated among young men in KwaZulu-Natal, South Africa. (December 2016) - Manyaapelo, Thabang; Ruiter, Robert; Nyembezi, Anam; van den Borne, Bart; Sifunda, Sibusiso; Reddy, Priscilla
Abstract Background A cross sectional study was conducted among 350 sexually active, mainly unemployed men between the ages of 18 and 35 in KwaZulu-Natal. This study examined the psychosocial determinants of the intention to be sexually active after having used marijuana or alcohol personally or in instances when the sexual partner is intoxicated. The theory of planned behaviour and cultural notions of responsible manhood were used in developing the measures. Methods Correlation and hierarchical stepwise linear regression analyses tested determinants of the intention to avoid having sex when personally intoxicated and the intention to avoid sex when the sexual partner is intoxicated. Results About 78 % of the participants reported regular use of alcohol and 39 % indicated ever-using marijuana. A total of 36.3 % used both alcohol and marijuana, and 73 % said that they engaged in multiple sexual partner behaviour. The intention to avoid sex when personally intoxicated as well as the intention to avoid sex when the sexual partner is intoxicated were significantly associated with subjective norms and perceptions of perceived behavioural control towards the respective behaviours, and less with attitudes towards the respective behaviours. Conclusions These findings imply that health education interventions should focus on changing the normative beliefs as well as control beliefs of the target population either directly through education and training or indirectly by creating physical and social environments that facilitate safe sexual practices, for example by organizing positive peer support for risk prevention and by making condoms freely available in community alcohol serving establishments.